Czy istnieje sezonowy rytm rozwoju w warunkach tropikalnych? (Raport 1 z dwuletnich comiesięcznych badań na Jukatanie w Meksyku) - Anna Siniarska; Armando Rojas; Graciela Valentin; Napoleon Wolański; Federico Dickinson (Studia Ecologiae et Bioethicae)
The main aim of this work concerns the answer to the question of whether the general regularity of seasonal differences in changes of height, weight, and body components during ontogeny in tropics exists. If so, whether this phenomenon depends on cyclic changes in nature or this rather is an adjustment to local conditions and mode of life.  To answer this question the studies took place in the tropical climate of Yucatan and included 49 boys and 47 girls aged 11-12 years and being of Maya, Mestizo, and Creole origin. The youths were attending two schools that were located in rather poor districts of Merida (the capital city of the Yucatan State, Mexico). The investigations started in February 2002 and ended in November 2003 and were continued monthly. The standard anthropometric methodology was applied to measure body height, weight, arm, waist, hip, and calf circumferences, and five subcutaneous fat folds (biceps and triceps brachii, subscapular, suprailiac and calf). Bioimpedance techniques were used to estimate fat mass (FM ), fat-free mass (FFM ), and total body water (TBW). The results show that general regularities in monthly or longer rates of stature increments and increments or declines of body mass do not exist. There are not similar regularities of changes even in groups of coevals of the same gender and within the youths coming from the same district. Each variable shows a quite specific rate of change.